Green Marketing and Attitude Affect the Consumer Buying Behavior of Green Product in Turkey - Akram Mohamad Alhamad; Essia Ries Ahmed; Mustafa Akyürek; Abdullah Mahfoud Salem Baadhem (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
Consumers are increasingly looking for natural goods to live more sustainably and healthily in recent years. As a result, firms have begun aligning their strategies with sustainability by emphasizing their production of natural products that are both beneficial for health and environmentally sustainable. However, there is a risk of deceptive claims being made. This is study focuses on determining consumer buying behavior regarding green products in Turkey, with an emphasis on the effect of green marketing and attitude on consumer buying behavior. The study integrates fundamental theoretical approaches to consumer buying, such as the theory of planned behavior (TPB), in a modified conceptual framework. A survey of 385 Turkish consumers knowledgeable about environmentally friendly green products was used to gather data, which was then analyzed using the SPSS 26 software. The results show that green marketing and attitudes have a significant influence on Turkish customers' consumer buying behavior.The findings of this study offer insight into theoretical approaches to consumer buying behavior for researchers and academicians and provide guidance for marketers in devising green marketing strategies to achieve optimal competitive advantage.